Die Bedeutung der übergemeindlichen Verbindungen im Urchristentum für die neutestamentliche Wissenschaft - Stenschke, Christoph W. 1966- (2019)
This article surveys subjects and questions in New Testament scholarship in the context of which scholars refer to the translocal links among early Christian communities and the people who embody them. Such references appear in comparisons between early Christian communities and ancient associations, in reconstructions of the history of early Christianity, in various issues of New Testament introduction (including the intended readers of the Gospels), in discussions of the material basis of theological diversity and unity in the New Testament and of the understanding of the church (the relationship between local community and the larger entity of the churches/the Church), and in studies of the argumentative strategies of New Testament books (new rhetoric, rhetorical criticism). In closing, the article refers to new questions and methods where translocal links provide important raw data or additional information, that is, various forms of social network analysis, issues of early Christian conceptions of space and the application of the questions and insights of critical spaciality. In view of the significance of the translocal links between early Christian communities for various issues in New Testament scholarship, it is surprising that they have not hitherto been examined comprehensively.
Keywords: Paul; ancient associations; co-workers of Paul; critical spaciality; Ecclesiology; history of early Christianity; readers of the Gospels; Social Network Analysis; theological diversity and unity in the New Testament; translocal links